ROC measures of memory accessibility. Issue 4 (April 2023) - Dubé, Chad
Laming has recently proposed a way to measure the accessibility (as opposed to availability) of memories via recognition testing. His measure "Accessibility" is calculated by subtracting the hit rate and false alarm rate that fall at the point where the receiver-operating characteristic (ROC) curve's derivative is 1. I prove that, if one works within the framework of Unequal-Variance Signal Detection Theory (UVSDT), as Laming does, the measure "Accessibility" depends on the location of the response criterion (though always with a neutral likelihood ratio). Furthermore, I prove that the measure varies with the underlying variances of UVSDT regardless of which definition of bias (criterion or likelihood ratio) is used and, crucially, this holds even when the accuracy of discrimination performance or "sensitivity"( d a ) in UVSDT is constant. As such, from the standpoint of (at least) UVSDT, it is questionable whether or to what extent the new measure of "Accessibility" actually measures the accessibility of any memory.